2023
DOI: 10.3390/ijms241411289
|View full text |Cite
|
Sign up to set email alerts
|

Melanin’s Journey from Melanocytes to Keratinocytes: Uncovering the Molecular Mechanisms of Melanin Transfer and Processing

Abstract: Skin pigmentation ensures efficient photoprotection and relies on the pigment melanin, which is produced by epidermal melanocytes and transferred to surrounding keratinocytes. While the molecular mechanisms of melanin synthesis and transport in melanocytes are now well characterized, much less is known about melanin transfer and processing within keratinocytes. Over the past few decades, distinct models have been proposed to explain how melanin transfer occurs at the cellular and molecular levels. However, thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 128 publications
0
19
0
Order By: Relevance
“…We previously proposed to name the mature melanin-containing compartment in keratinocytes melanokerasome (MKS) (Moreiras et al, 2021;. Bento-Lopes et al, 2023). After establishing that this compartment is positive for late endosomal and lysosomal markers using relatively long chase periods (up to 24 hours), we next aimed to address whether MKSs are formed by fusion with a pre-existing lysosomal compartment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously proposed to name the mature melanin-containing compartment in keratinocytes melanokerasome (MKS) (Moreiras et al, 2021;. Bento-Lopes et al, 2023). After establishing that this compartment is positive for late endosomal and lysosomal markers using relatively long chase periods (up to 24 hours), we next aimed to address whether MKSs are formed by fusion with a pre-existing lysosomal compartment.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated that melanocore internalization by keratinocytes occurs by phagocytosis, leading to the formation of a melanin-containing storage compartment, which we proposed to be named melanokerasome (MKS) (Moreiras et al, 2021;. Bento-Lopes et al, 2023). MKSs were found by us and others to be weakly acidic and weakly degradative (Correia et al, 2018; Hurbain et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of HEK sEVs to promote pigment transfer suggests that sEVs are crucial actors in mediating pigment exchange between these two epidermal cell types. Although the mechanisms of pigment transfer are still debated (30, 31), the generation of dendrites in HEMs is a prerequisite for the establishment of physical contacts with HEKs, while also crucial cellular structures for pigment positioning, enrichment, and transfer, further supporting that sEVs-induced HEM plasticity is pivotal to support these pigmentary functions. In agreement, maintaining the capacity of HEMs to remodel their plasma membrane and to contact HEKs is key for melanin transfer (32).…”
Section: Discussionmentioning
confidence: 99%
“…Phototherapy affects immune cells (cytotoxic and regulatory T cells), keratinocytes, melanocytes and fibroblasts, and their function targeting both stabilization and repigmentation. 26,137,138,139,140 NBUVB led to decreased frequencies of circulating CD4+ and CD8+ central memory T cells, suggesting a potential immunosuppressive effect, while also down-regulating chemokines CXCL9 and CXCL10, which play a crucial role in the homing of memory T cells to vitiligo lesions. 141 In active NSV, patients exhibited higher levels of circulating CD4(+) CD25(high) Tregs and Foxp3(+) Tregs compared to healthy controls (studies regarding Tregs in vitiligo report variable results, especially regarding the circulating vs. skin resident cells) [142][143][144] and NB-UVB therapy decreased these levels in patients suggesting a potential impact on Tregs function.…”
Section: Molecul Ar a S Pec Ts Of Vari Ous Photother Apy Tre Atments ...mentioning
confidence: 97%
“…Phototherapy affects immune cells (cytotoxic and regulatory T cells), keratinocytes, melanocytes and fibroblasts, and their function targeting both stabilization and repigmentation 26,137,138,139,140 . NBUVB led to decreased frequencies of circulating CD4+ and CD8+ central memory T cells, suggesting a potential immunosuppressive effect, while also down‐regulating chemokines CXCL9 and CXCL10, which play a crucial role in the homing of memory T cells to vitiligo lesions 141 .…”
Section: Molecular Aspects Of Various Phototherapy Treatments In Viti...mentioning
confidence: 99%